Timing of diagnosis affects mortality in critical congenital heart disease. Issue 6 (30th June 2015) - Eckersley, Luke; Sadler, Lynn; Parry, Emma; Finucane, Kirsten; Gentles, Thomas L
Abstract : Objective: Screening for critical congenital heart disease (CHD) with prenatal ultrasound or postnatal pulse oximetry has the potential to improve outcome. To guide screening recommendations, this study aimed to identify the proportion and outcome of major CHD diagnosed before (early) or after (late) postnatal discharge prior to the introduction of postnatal oximetry screening. Design: A retrospective, population-based review of all major CHD in New Zealand from 2006 to 2010. The timing of diagnosis relative to discharge and to intervention in critical and non-critical cases with intention to treat was determined, as was the relationship of diagnostic timing to mortality at 1 year of age. Results: Late diagnosis occurred in 20% of critical and 51% of non-critical cases. Mortality occurred in 18% of critical vs 8% of non-critical cases. Mortality was lower with an early diagnosis of critical CHD (early diagnosis 16% vs late diagnosis 27%, p=0.04). Isolated critical CHD benefited most from early diagnosis (mortality, early diagnosis 12% vs late diagnosis 29%, p=0.002). Early diagnosis occurred in >90% critical complex CHD and hypoplastic left heart syndrome, 85% d-transposition of the great arteries (d-TGA) and 53% critical left ventricular outflow tract obstruction (LVOTO). Deaths in d-TGA and LVOTO primarily occurred prior to intervention and for d-TGA most often when birth was distant from the cardiac centre. Conclusions: Excess mortality occurs following late diagnosis of critical CHD, and for d-TGA even with early diagnosis if intervention is not immediately available. Antenatal detection retains an important role in reducing mortality related to critical CHD.